Fatigue and biological properties of Ti-6Al-4V ELI cellular structures with variously arranged cubic cells made by selective laser melting. (February 2018) - Dallago, M.; Fontanari, V.; Torresani, E.; Leoni, M.; Pederzolli, C.; Potrich, C.; Benedetti, M.
Abstract: Traditional implants made of bulk titanium are much stiffer than human bone and this mismatch can induce stress shielding. Although more complex to produce and with less predictable properties compared to bulk implants, implants with a highly porous structure can be produced to match the bone stiffness and at the same time favor bone ingrowth and regeneration. This paper presents the results of the mechanical and dimensional characterization of different regular cubic open-cell cellular structures produced by Selective Laser Melting (SLM) of Ti6Al4V alloy, all with the same nominal elastic modulus of 3 GPa that matches that of human trabecular bone. The main objective of this research was to determine which structure has the best fatigue resistance through fully reversed fatigue tests on cellular specimens. The quality of the manufacturing process and the discrepancy between the actual measured cell parameters and the nominal CAD values were assessed through an extensive metrological analysis. The results of the metrological assessment allowed us to discuss the effect of manufacturing defects (porosity, surface roughness and geometrical inaccuracies) on the mechanical properties. Half of the specimens was subjected to a stress relief thermal treatment while the other half to Hot Isostatic Pressing (HIP), and we compared the effect of the treatments on porosity and on the mechanical properties. Fatigue strength seems to be highly dependent on the surface irregularities and notches introduced during the manufacturing process. In fully reversed fatigue tests, the high performances of stretching dominated structures compared to bending dominated structures are not found. In fact, with thicker struts, such structures proved to be more resistant, even if bending actions were present. Highlights: Fatigue strength of cellular structures is affected mainly by sharp notches. Thicker cell wall junctions improve fatigue resistance. Bending actions in the cell walls allow thicker junctions at the same stiffness. Regular cubic structures showed better cellular proliferation.